2014
DOI: 10.1371/journal.pone.0106093
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenies of Microcystin-Producing Cyanobacteria in the Lower Laurentian Great Lakes Suggest Extensive Genetic Connectivity

Abstract: Lake St. Clair is the smallest lake in the Laurentian Great Lakes system. MODIS satellite imagery suggests that high algal biomass events have occurred annually along the southern shore during late summer. In this study, we evaluated these events and tested the hypothesis that summer bloom material derived from Lake St. Clair may enter Lake Erie via the Detroit River and represent an overlooked source of potentially toxic Microcystis biomass to the western basin of Lake Erie. We conducted a seasonally and spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 59 publications
5
40
0
Order By: Relevance
“…The phytoplankton phyla composition observed in this study was also found in other investigated Ohio lakes such as lake Erie [20] and other smaller lakes [6] [21]. The dominance of Cyanobacteria, which was also observed in a number of Ohio lakes [6], could be typical for summer algal blooms.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The phytoplankton phyla composition observed in this study was also found in other investigated Ohio lakes such as lake Erie [20] and other smaller lakes [6] [21]. The dominance of Cyanobacteria, which was also observed in a number of Ohio lakes [6], could be typical for summer algal blooms.…”
Section: Discussionsupporting
confidence: 83%
“…The phylogenetic similarity of potentially toxic species M. aeruginosa among Harsha Lake and other adjacent waters, such as Lake St. Clair, Lake Erie and Lake Ontario, indicates its broad presence. It should be noticed that the fragment of mcyA gene may not reflect high diversity of the amplicons as observed in previous study [20], due to the little variable region of mcyA assay included in its short sequence (230 bp). Davis et al .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, it is possible that, in the future, the CMS may update its position, although currently there is no definitive timeline for any changes. Understanding the characteristics of the facility's source water will allow the medical director, biomedical technician, and clinical team to create a practical and effective quality assurance plan in the event that the source water is compromised because of natural or manmade disasters (Table 3) (6)(7)(8). Appropriately, any quality assurance plan should identify backup water sources for emergencies (9).…”
Section: Know Your Source Watermentioning
confidence: 99%
“…Miller, Beversdorf, Chaston, and McMahon (2013) and Beversdorf, Miller, and McMahon (2013) also studied this system and found spatial variability of community composition within and between lakes. Davis et al (2014) explored genetic connectivity of Microcystis aeruginosa in Lakes St. Clair, Erie and Ontario using the mcyA toxin gene. They found six groups at 99% identity that were present throughout the system, suggesting high connectivity.…”
Section: Introductionmentioning
confidence: 99%